Collaborative Governance Model on The Guidance of Terrorist Parolees (Case Study in Surakarta Parole Office) - Budiyanto, Sigit; Nurdin, Nurliah; Utomo, Tri Widodo Wahyu; Sutrisno, Edy; Karunia, R. Luki (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
This research delves into the collaborative governance framework concerning the reintegration guidance of terrorist parolees, as exemplified by the Surakarta Parole Office. Terrorism, a global concern, is defined as a criminal undertaking intended to overtly propagate fear and panic, perpetrated by specific factions either for ideological or distinct political motives. Addressing terrorism necessitates the concerted efforts of multiple stakeholders. Within the realm of Corrections, Parole Offices assume the responsibility of aiding terrorist parolees in their societal reintegration. However, the current level of collaboration between the Parole Office and stakeholders in this particular endeavor remains suboptimal. This study aims to identify the factors contributing to this issue, employing a qualitative methodology with a descriptive orientation. Through meticulous data analysis, it is revealed that collaborative governance in the context of guiding terrorist parolees within the Surakarta Parole Office is not functioning at its full potential due to several factors, aligned with the four dimensions of Ansell and Gash's (2007) collaborative governance model, namely Starting Conditions, Collaborative Process, Facilitative Leadership, Institutional Design, and Outcome. To optimize the collaborative framework for guiding terrorist parolees, this research proposes an enhanced collaborative governance model building upon the foundation laid by Ansell and Gash. This model advocates for a comprehensive collaborative approach involving pertinent multi-actors.